2012
DOI: 10.1208/s12249-012-9858-4
|View full text |Cite
|
Sign up to set email alerts
|

The Investigation on Polyion Complex Micelles Composed of Diammonium Glycyrrhizinate/Poly(Ethylene Glycol)–Glycidyltrimethylammonium Chloride-Grafted Polyasparthydrazide

Abstract: Abstract. To prepare stable polyion complex (PIC) micelles, polyasparthydrazide (PAHy) modified with glycidyltrimethylammonium groups and methoxy poly(ethylene glycol) (mPEG) (mPEG-g-PAHy-GTA) was synthesized. The cytotoxicity of the polymer was evaluated by the methyl tetrazolium assay. The polymer entrapped the diammonium glycyrrhizinate (DG) and formed polyion complexes. The effect of pH value, grafting degree of mPEG, copolymer and drug concentration on the micelle formation was investigated by means of me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The ratio of GTA grafted onto PAHy side chain was defined as the grafting degree (GD, mol%) (GD of GTA = trimethylammonium groups/the L-aspartic acid units). The grafting degree was 32% as reported before [14].…”
Section: Synthesis Of Polymersmentioning
confidence: 71%
See 2 more Smart Citations
“…The ratio of GTA grafted onto PAHy side chain was defined as the grafting degree (GD, mol%) (GD of GTA = trimethylammonium groups/the L-aspartic acid units). The grafting degree was 32% as reported before [14].…”
Section: Synthesis Of Polymersmentioning
confidence: 71%
“…PAHy-GTA was synthesized and characterized according to the previously reported procedure [14]. Briefly, polysuccimide (PSI) was synthesized by the polycondensation of L-aspartic acid [17].…”
Section: Synthesis Of Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…Incorporation of PEG-CG during micelle formation could strongly affect the micelle-DNA interactions, as both particle size and zeta potential were altered at the presence of PEG-CG. It has been suggested that the PEG corona could prevent the aggregation of micelles or micellebased nanocomposites due to a steric repulsion between the PEG chains [42][43][44][45]. This may explain that sizes of polyplex particles containing PEG-CG were smaller than those without PEG-CG for most of the N/P ratios ( Fig.…”
Section: Characterization Of Polymer/dna Polyplexesmentioning
confidence: 97%